Polymorphisms in HLA-related genes and psoriasis heredity in patients with psoriasis - Vasku, Anna; Bienertova-Vasku, Julie; Izakovicova-Holla, Lydie; Pavkova Goldbergova, Monika; Kozacikova, Zuzana; Splichal, Zbynek; Vasku, Vladimir (International journal of dermatology, 2013)
BACKGROUND: The aim of this study was to investigate possible associations of the five DNA polymorphic genotypes in the HLA region (transporter associated with antigen processing [TAP1; TAP1 333 a/b, TAP1 637 c/d], the HLA-DRB1*1501-rs3135388, tumor necrosis factor [TNF]α [-238 G/A] and NcoI TNFβ) with characteristics of family history in patients with psoriasis vulgaris. MATERIALS AND METHODS: A total of 201 Czech patients with psoriasis were enrolled in the study. The patients were genotyped for the five common polymorphisms in TAP1, TNFα, and TNFβ genes (6p21.3) using the polymerase chain reaction-restriction fragment length polymorphism-based methodology. RESULTS: We observed significantly higher prevalence of Ile333Ile TAP1 allele in patients whose first-degree relatives had a positive family history of psoriasis (Pa = 0.04). No differences related to family history of psoriasis were observed in HLA-DRB1*1501 polymorphism. As for the TNFα (-238 G/A) polymorphism, a significant increase of the GG genotype was observed in patients, especially men with second- and third-degree relatives with psoriasis (Pg = 0.008). Similarly, the B2B2 genotype of NcoI TNFβ polymorphism was more frequent in psoriatic patients, especially women, whose second- and third-degree relatives had psoriasis (Pg = 0.004). Finally, the haplotype analysis of all five polymorphisms revealed that the frequency of haplotype bcCB1A was different between not only men and women with psoriasis (P = 0.007) but also between men and women without a family history of psoriasis (P = 0.007). CONCLUSIONS: Haplotype association of HLA gene polymorphisms with genealogy aspects of psoriasis facilitates a better understanding of etiopathogenetic aspects of the diseases.
Keywords: haplotypy; Humans; Polymorphism, Restriction Fragment Length; lidé středního věku; lymfotoxin-alfa; HLA-DRB1 řetězec; polymorfismus genetický; Psoriasis; Female; ABC transportéry; rizikové faktory; dospělí; Aged; psoriáza; Haplotypes; senioři; lidé; HLA-DRB1 Chains; ATP Binding Cassette Transporter, Subfamily B, Member 2; Polymorphism, Genetic; TNF-alfa; Adult; ženské pohlaví; ATP-Binding Cassette Transporters; Male; Middle Aged; peptidový transportér TAP1; Genetic Predisposition to Disease; genetická predispozice k nemoci; zdraví rodiny; Tumor Necrosis Factor-alpha; polymorfismus délky restrikčních fragmentů; Family Health; mužské pohlaví; Lymphotoxin-alpha; Risk Factors